Organizational cognitive neuroscience and its applications in the workplace: An analysis of the perception of leaders - Duarte, Heriton Mascarelo; Cabral, Patrícia Martins Fagundes; Freitas Junior, José Carlos da Silva; Milan, Gabriel Sperandio; de David, Cíntia de (Open Science Journal, 2024)
This paper analyzes the perception of leaders about the discoveries of organizational cognitive neuroscience (OCN) and their practical applications in the work environment, as well as identifying gaps and distortions of knowledge that leaders have about this area of study. Based on a study with the participation of one hundred and thirty-six respondents, of which part consider themselves in leadership positions, conducted in two stages, using a quantitative and qualitative method, it was possible to highlight the perception of such leaders about the practices currently used in their companies, even though they are unaware of the neurological factors and reflexes that trigger them. The results also made it possible to propose initiatives and actions for leaders regarding the expansion of knowledge about NCO. Finally, this research presents recommendations for including or changing internal and external leadership training programs on the topics covered in Organizational Cognitive Neuroscience.